The Use of Radio Telemetry as an Aid in the Retrieval of Bowhead Whales (Balaena Mysticetus) Struck during the Annual Eskimo Subsistence Hunt in Alaska - Follmann, Erich H.; Manning, Arthur E. (ARCTIC, 1989)
Over past years the number of bowhead whales struck and lost during the annual subsistence hunt by Eskimos in northern Alaska has averaged about 50%. This is a significant number of lost animals, especially for a species considered to be rare and endangered, and steps must be taken to reduce this loss. A project was initiated in 1983 to determine the feasibility of using radio telemetry to aid in the recovery of bowhead whales struck during the subsistence hunt. The radio transmitter was placed in the whaling float to minimize the problem of signal attenuation by marine waters. The stainless steel attachment plates worked flawlessly to stabilize the radio transmitter inside the float and to seal the hole cut in the float to insert the radio transmitter. With directional receiving antennas and receivers, floats could be detected at several kilometres from boats and at over 40 km from aircraft. Fifteen whaling crews were instrumented for the fall subsistence hunts beginning in 1983 at Kaktovik and in 1986 at Nuiqsut. Eight of 12 whales struck were retrieved during the course of this study, 2 of the 8 because they were found by virtue of the radio signals transmitted from the floats 11 and 48 km offshore. Floats attached to the 4 whales that were lost during this period were radio-located but the harpoons had pulled out of 2 of these whales. The other two floats were not attached to whales when found and the distances from shore were too far to safely retrieve the equipment to determine the exact reason for loss. A 67% retrieval rate was achieved during this study, up from 50% had radio telemetry not been used. Radio telemetry has proven to be a successful technique to support the subsistence hunt for the bowhead whale, and the Alaska Eskimo Whaling Commission is currently expanding its use to other villages where relatively ice-free waters are conducive to its use.Key words: bowhead whale, Balaena mysticetus, Eskimo subsistence hunt, Alaska, radio telemetry Mots clés: baleine franche, Balaena mysticetus, chasse ...